Characterization of Phase Structures of Novel Metallo‐Polyurethanes. Issue 20 (21st September 2015) - Lucio, Beatriz; de la Fuente, José Luis; Cerrada, María L.
<x xml:space="preserve">Abstract</x> Two series of chemically well‐defined polyurethanes (PUs) have been synthesized containing two different soft segments of interest in aerospace applications. At a given soft fragment, four different hard segments (HSs) based on single diisocyanate molecules with no chain extenders have been incorporated. Both segmented PU series have been prepared by stoichiometric reactions of the macrodiol hydroxyl‐terminated polybutadiene (HTPB), and a metallo‐derived, this being the (ferrocenylbutyl) dimethylsilane grafted on HTPB, so‐called Butacene. Those HSs are isophorone diisocyanate, toluene‐2, 4‐diisocyanate, 4, 4′‐diphenyl methane diisocyanate, and hexamethylene diisocyanate. Microphase separation and morphology development have been studied at room temperature in these copolymers using Fourier transform infrared spectroscopy, analyzing the change in the relative intensities of free and hydrogen‐bonded carbonyl peaks. Measurements of wide‐ and small‐angle X‐ray diffraction using synchrotron radiation allow analyzing the morphological and microstructural differences between these two series of samples. In addition, dynamic mechanical analysis and differential scanning calorimetry have been used to learn about the relaxation processes and thermal transitions that are observed in these materials and to confirm the existence or lack of phase segregation. The knowledge of structure–property relationship is very important in these advanced organometallic PUs to get an understanding of their application as solid composite propellants binder.